Star Wars : the legends of Luke Skywalker - Liu, Ken, 1976- (Journey to Star wars: the last Jedi., 2017)
"As a cargo ship rockets across the galaxy to Canto Bight, the deckhands on board trade stories about legendary Jedi Knight Luke Skywalker. But are the stories of iconic and mysterious Luke Skywalker true, or merely tall tales passed from one corner of the galaxy to another? Is Skywalker really a famous Jedi hero, an elaborate charlatan, or even part droid? The deckhands will have to decide for themselves when they hear The Legends of Luke Skywalker, a collection of myths and tall-tales about the legendary Jedi Luke Skywalker"--Amazon.